2014
DOI: 10.1371/journal.pone.0089680
|View full text |Cite
|
Sign up to set email alerts
|

A Selected Core Microbiome Drives the Early Stages of Three Popular Italian Cheese Manufactures

Abstract: Mozzarella (M), Grana Padano (GP) and Parmigiano Reggiano (PR) are three of the most important traditional Italian cheeses. In the three cheese manufactures the initial fermentation is carried out by adding natural whey cultures (NWCs) according to a back-slopping procedure. In this study, NWCs and the corresponding curds from M, GP and PR manufactures were analyzed by culture-independent pyrosequencing of the amplified V1–V3 regions of the 16S rRNA gene, in order to provide insights into the microbiota involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,201 publications
(104 citation statements)
references
References 60 publications
5
93
1
1
Order By: Relevance
“…Genes with high polymorphism within a species can be selected for this application, potentially allowing discrimination between different strains within a species (Ercolini et al ., 2013). In spite of the limitations due to possible sequencing errors, this application was recently exploited for monitoring Streptococcus thermophilus in whey and milk cultures and in cheeses, using lactose permease ( lacS , De Filippis et al ., 2014) and phosphoserine phosphatase ( serB , Parente et al ., 2016b; Ricciardi et al ., 2016) as species‐specific and polymorphic target genes.…”
Section: Monitoring Microbes In Food Fermentationsmentioning
confidence: 99%
“…Genes with high polymorphism within a species can be selected for this application, potentially allowing discrimination between different strains within a species (Ercolini et al ., 2013). In spite of the limitations due to possible sequencing errors, this application was recently exploited for monitoring Streptococcus thermophilus in whey and milk cultures and in cheeses, using lactose permease ( lacS , De Filippis et al ., 2014) and phosphoserine phosphatase ( serB , Parente et al ., 2016b; Ricciardi et al ., 2016) as species‐specific and polymorphic target genes.…”
Section: Monitoring Microbes In Food Fermentationsmentioning
confidence: 99%
“…Studies on other cheeses, using pyrosequencing to gain insight into their microbiota, have also led to the definition of a common core microbiota in several cheese-making units within the same broad geo-graphic area (De Filippis et al, 2014;Fuka et al, 2013;Quigley et al, 2012). The naturally-selected core microbiome is fundamental for the maturation process in artisanal, regional cheeses.…”
Section: Identification Of Core Bacterial Community Members and Abundmentioning
confidence: 99%
“…These methods have been recently used in other dairy products, demonstrating the feasibility of generating deeply sequenced metagenomes for microbial identification and to study the dynamics of microbial communities (review by Bokulich and Mills, 2012;Ercolini, 2013). Recent studies in microbial diversity in cheeses (De Filippis et al, 2014;Ercolini et al, 2012;Masoud et al, 2011) and more specifically artisanal cheeses (Aldrete-Tapia et al, 2014;Alegría et al, 2012;Fuka et al, 2013;Quigley et al, 2012) have validated the application of this methodology in community screening to unravel the microbial structure and to detect determinants of safety and quality in cheese (Lusk et al, 2012;Montel et al, 2014;O'Sullivan et al, 2013). Pyrosequencing was chose for its sensitivity, which provided great sequence coverage and allowed to obtain a complete picture of the diverse microbial communities involved at the different fermentation times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies performed on these products showed that the dominant microorganisms belong to the lactic acid bacteria [12]- [16]. Therefore, the objective of the current study here to isolate and identify new probiotic candidates in a bacterial collection obtained from São Jorge and Parmigiano-Reggiano cheeses.…”
Section: Introductionmentioning
confidence: 99%